2015
DOI: 10.1680/jmacr.14.00163
|View full text |Cite
|
Sign up to set email alerts
|

Shear capacity of RC beams at elevated temperatures

Abstract: Fire safety is a critical criterion for designing reinforced concrete structures. With the introduction of performancebased design, structural engineers need design tools to assess the capacity of different elements during fire exposure. This paper proposes an analytical method to predict the shear capacity of reinforced concrete beams exposed to elevated temperatures. The proposed method extends the use of existing ambient temperature methods by accounting for the effect of elevated temperatures on material p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…the calculation methods … are not fully verified», Annex D, EN 1992-1-2:2004, as the number of experimental and numerical studies on shear and torsion in fire is fairly limited (as recently observed by Youssef et al, 2015) and often focused on special structures. (A few examples on shear: Felicetti and Gambarova, 1999 for deep beams; Fellinger et al, 2005, andMsaad andChefdebien, 2007, for hollow-core slabs;Hertz, 1985, Taerwe et al, 2006, Kodur and Hatinger, 2011, and Bamonte et al, 2011 for P/C beams; Smith et al, 2011, andYoussef et al, 2015 for R/C beams; Faria et al, 2010, andKotsovos andKotsovos, 2013 for R/C frames and linear members; Lim et al, 2004, andAli andNadjai, 2011 for slabs. On the contrary, many are the studies on bending and axial loading (Kordina, 1979;Ellingwood and Lin, 1991;Desai, 1998); Hsu and Lin, 2008;El-Fitiany and Youssef, 2009, just to cite a few).…”
Section: Design Models In Shear and Torsionmentioning
confidence: 99%
See 1 more Smart Citation
“…the calculation methods … are not fully verified», Annex D, EN 1992-1-2:2004, as the number of experimental and numerical studies on shear and torsion in fire is fairly limited (as recently observed by Youssef et al, 2015) and often focused on special structures. (A few examples on shear: Felicetti and Gambarova, 1999 for deep beams; Fellinger et al, 2005, andMsaad andChefdebien, 2007, for hollow-core slabs;Hertz, 1985, Taerwe et al, 2006, Kodur and Hatinger, 2011, and Bamonte et al, 2011 for P/C beams; Smith et al, 2011, andYoussef et al, 2015 for R/C beams; Faria et al, 2010, andKotsovos andKotsovos, 2013 for R/C frames and linear members; Lim et al, 2004, andAli andNadjai, 2011 for slabs. On the contrary, many are the studies on bending and axial loading (Kordina, 1979;Ellingwood and Lin, 1991;Desai, 1998); Hsu and Lin, 2008;El-Fitiany and Youssef, 2009, just to cite a few).…”
Section: Design Models In Shear and Torsionmentioning
confidence: 99%
“…The above-mentioned models, however, have not been validated in fire conditions [Eurocode 2 - EC2 (EN 1992-1-2) (2005): «shear – and torsion – failures due to fire are very uncommon […]. the calculation methods […] are not fully verified», Annex D, EN 1992-1-2, 2004], as the number of experimental and numerical studies on shear and torsion in fire is fairly limited as recently observed by Youssef et al (2015) and often focused on special structures [A few examples on shear: Felicetti and Gambarova (1999) for deep beams; Fellinger et al (2005) and Msaad and Chefdebien (2007) for hollow-core slabs; Hertz (1985), Taerwe et al (2006), Kodur and Hatinger (2011) and Bamonte et al (2011) for P/C beams; Smith et al (2011) and Youssef et al (2015) for R/C beams; Faria et al (2010) and Kotsovos and Kotsovos (2013) for R/C frames and linear members; Lim et al (2004) and Ali and Nadjai (2011) for slabs. On the contrary, many are the studies on bending and axial loading (Kordina, 1979; Ellingwood and Lin, 1991; Desai, 1998; Hsu and Lin, 2008; El-Fitiany and Youssef, 2009), just to cite a few].…”
Section: Design Models In Shear and Torsionmentioning
confidence: 99%
“…614 In the case of RC beams, unlike the extensive research performed to understand the performance of RC beams exposed to creep and shrinkage, a few studies have been carried out on the effect of moderate to high temperature on the short-term behavior of RC beams. 1524…”
Section: Introductionmentioning
confidence: 99%
“…The literature contains many studies that have investigated the effect of fire on RC structural members, such as beams, 25–30 slabs, 31–34 or tunnel linings 35–38 . Despite all the research available, new recommendations and approaches for the design and assessment of concrete structures and structural components to protect against fire are still being published to this day 8,39–42 .…”
Section: Introductionmentioning
confidence: 99%